Effect of active silica on performance of maize (Zea mays) under organic farming - PRAJAPAT, BHAWANI SINGH; KAUSHIK, M K; SHARMA, S K; CHAUDHARY, R; YADAV, S K; MEENA, S N; MEENA, R L; NAIK, B SRI SAI SIDDARTHA (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during kharif 2018-19 at Organic Unit of Instructional Farm, Rajasthan College of Agriculture, Maharana Pratap University of Agriculture and Technology, Udaipur, Rajasthan. The experiment consisting of six soil applications in main plots (0, 50, 75, 100, 125 and 150 kg/ha) and six foliar applications of active silica in sub plots (no spray, water spray, 0.25, 0.50, 0.75 and 1.0%) was carried out in split-plot design with three replications. Results indicated that significantly higher number of rows/cob, number of grains/row, test weight, grain, stover and biological yield was recorded with 150 kg/ha active silica application. Similarly, higher protein content in grain, Si content and uptake by plant at 60, 75 DAS and harvest, and N, P and K content and uptake in grain as well in stover was recorded at 150 kg/ha active silica application. Among foliar application, the spray of 1.0% active silica significantly enhanced the yield attributes, yield, protein content in grain, Si content and uptake by plant at 60, 75 DAS and harvest; and N, P and K content and uptake in grain as well in stover in maize (Zea mays L.) under organic production system.